Numerical evaluation (FEA) of end stop impact forces for a crane fitted with hydraulic buffers - Idowu,Ifeolu Mobolaji (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScEng (Civil Engineering))--University of Stellenbosch, 2010.